Mas Receptor Blockade Promotes Renal Vascular Response to Ang II after Partial Kidney Ischemia/Reperfusion in a Two-Kidney-One-Clip Hypertensive Rats Model - Farzaneh Karimi; Mehdi Nematbakhsh (International Journal of Nephrology)
Background. Partial kidney ischemia-reperfusion (IR) injury is the principal cause of acute kidney injury. The renin-angiotensin system (RAS) and hypertension also may be influenced by renal IR injury. In two models of partial renal IR with and without ischemia preconditioning (IPC) and using Mas receptor (MasR) blockade, A779 or its vehicle, the renal vascular responses to angiotensin II (Ang II) administration in two-kidney-one-clip (2K1C) hypertensive rats were determined. Methods. Thirty-seven 2K1C male Wistar rats with systolic blood pressure ≥150 mmHg were randomly divided into three groups; sham, IR, and IPC + IR. The animals in the sham group underwent surgical procedures except partial IR. The rats in the IR group underwent 45 min partial kidney ischemia, and the animals in the IPC + IR group underwent two 5 min cycles of partial kidney ischemia followed by 10 min reperfusion and partial kidney ischemia for 45 min. The renal vascular responses to graded Ang II (30, 100, 300, and 1000 ng kg−1.min−1) infusion using A779 or its vehicle were measured at constant renal perfusion pressure. Results. Four weeks after 2K1C implementation, the intravenous infusion of graded Ang II resulted in dose-related increases in mean arterial pressure (MAP) (Pdose < 0.0001) that was not different significantly between the groups. No significant differences were detected between the groups in renal blood flow (RBF) or renal vascular resistance (RVR) responses to Ang II infusion when MasR was not blocked. However, by MasR blockade, these responses were increased in IR and IPC + IR groups that were significantly different from the sham group (P < 0.05). For example, infusion of Ang II at dose 1000 ng kg−1.min−1 resulted in decreased RBF percentage change (RBF%) from the baseline to 17.5 ± 1.9%, 39.7 ± 3.8%, and 31.0 ± 3.4% in sham, IR, and IPC + IR, respectively. Conclusion. These data revealed the important role of MasR after partial kidney IR in the responses of RBF and RVR to Ang II administration in 2K1C hypertensive rats.